Becoming academics: embracing and resisting changing writing practice. Issue 3 (18th September 2019) - Katila, Saija; Laamanen, Mikko; Laihonen, Maarit; Lund, Rebecca; Meriläinen, Susan; Rinkinen, Jenny; Tienari, Janne
Abstract : Purpose: The purpose of this paper is to analyze how global and local changes in higher education impact upon writing practices through which doctoral students become academics. The study explores how norms and values of academic writing practice are learned, negotiated and resisted and elucidates how competences related to writing come to determine the academic selves. Design/methodology/approach: The study uses memory work, which is a group method that puts attention to written individual memories and their collective analysis and theorizing. The authors offer a comparison of experiences in becoming academics by two generational cohorts (1990s and 2010s) in the same management studies department in a business school. Findings: The study indicates that the contextual and temporal enactment of academic writing practice in the department created a situation where implicit and ambiguous criteria for writing competence gradually changed into explicit and narrow ones. The change was relatively slow for two reasons. First, new performance management indicators were introduced over a period of two decades. Second, when the new indicators were gradually introduced, they were locally resisted. The study highlights how the focus, forms and main actors of resistance changed over time. Originality/value: The paper offers a detailed account of how exogenous changes in higher education impact upon, over time and cultural space, academic writing practices through which doctoral students become academics.